Comparative Analysis of Consumer Preferences for Meatballs with 70% Barracuda Fish (Sphyraena barracuda) and 9% Seaweed (Kappaphycus alvarezii) - Cangara, Arie Syahruni; Suro Adhawati, Sri; Amiluddin, Amiluddin; Audy Jaya Gosari, Benny; Sudrajat, Iman; Mughsita Sani, Andi Nadia (Torani Journal of Fisheries and Marine Science, 2024)
This study aims to analyze consumer preferences for meatballs formulated with 70% barracuda fish (Sphyraena barracuda) and 9% seaweed (Kappaphycus alvarezii), and to compare them with conventional meatballs. The method used is an organoleptic test involving 20 respondents in Makassar City. Respondents assessed four main aspects: taste, aroma, texture, and appearance, using a Likert scale (1–5). Descriptive analysis results show that barracuda fish meatballs scored higher in texture (4.0) compared to conventional meatballs (3.7), while conventional meatballs were superior in taste (4.5 versus 4.2). The t-test results indicate that the difference in texture is significant (p < 0.05), whereas the differences in taste, aroma, and appearance are not significant (p > 0.05). Overall, meatballs made with barracuda fish and seaweed have potential for commercial development, especially as a healthier alternative with optimal nutritional value.